A necessarily better place: Images of New Zealand in the Slovak mass media. Issue 1 (1st April 2013) - Barrer, Peter
New Zealand and Slovakia have some things in common in spite of their distance from each other. Both countries have similarly sized populations and national identities attached to strong agricultural heritages. Also, both countries have faced isolation – New Zealand's geographical 'tyranny of distance' and Slovakia's one-time political position at 'the forgotten centre' of Europe. Although bilateral economic, political and person-to-person links between the two countries are on a negligible level, Slovaks certainly know of New Zealand even if very few have actually been there; their knowledge and image of the country is primarily constructed from the Slovak mass media. This article examines the image of New Zealand in the Slovak mass media from 2010 to 2012: a period which saw the first ever football encounter between the two countries at the 2010 FIFA World Cup in South Africa, as well as an event in New Zealand (the February 2011 Christchurch earthquake) which was covered by the Slovak media. The images of New Zealand presented herein will contribute to the wider discussion of popular perceptions of New Zealand in the region of central Europe.